2020
DOI: 10.1111/cbdd.13765
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin activates Nrf2/Keap1 signaling to protect neuronal cells from oxidative stress

Abstract: Oxidative stress is closely related to brain aging and development of various neurodegenerative disorders, including Alzheimer's disease, Parkinson's disease, and brain stroke (Allen & Bayraktutan, 2009; Okazawa, Ikawa, Tsujikawa, Kiyono, & Yoneda, 2014). The brain is extremely intolerant to oxidative stress because of its high demand for oxygen and the presence of large amounts of unsaturated lipids (Cutler et al., 2004). Reactive oxygen species (ROS), the most important oxygen free radical, is closely relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…29 More importantly, recent evidence has shown a close correlation between oxidative stress and cell apoptosis. 30 During the cerebral ischemia, ROS could induce the neuronal apoptosis via many pathways. 31,32 In this work, we found that after cerebral I/R injury, CBX7 -/mice had a decrease in the content of MDA but increases in the SOD activity and content of GSH-PX and CAT, presenting with a decrease in the cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…29 More importantly, recent evidence has shown a close correlation between oxidative stress and cell apoptosis. 30 During the cerebral ischemia, ROS could induce the neuronal apoptosis via many pathways. 31,32 In this work, we found that after cerebral I/R injury, CBX7 -/mice had a decrease in the content of MDA but increases in the SOD activity and content of GSH-PX and CAT, presenting with a decrease in the cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We also speculate that the mechanism is related to the antioxidant capacity of ICT based on existing experiments and related research. A large number of studies have shown that ICT is a relatively good plant-based antioxidant and it has good antioxidant capacity in different cell and animal experiments ( Liu et al, 2014 ; Xu et al, 2021 ). This experiment also showed that ICT can improve the levels of oxidative stress indicators to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…It improves learning and memory, fights inflammation, scavenges oxygen free radicals, slows aging and protects neuronal function ( Feng et al, 2019 ; Hao et al, 2019 ; Wang et al, 2007 ). Studies have shown that ICT can protect neurons by ameliorating mitochondrial damage and oxidative stress ( Wu et al, 2021 ; Xu et al, 2021 ). Therefore, we hypothesized that ICT can alleviate energy metabolism disorder in the brain and that its mechanism might be related to a reduction in TDP-43 expression.…”
Section: Introductionmentioning
confidence: 99%
“…ICA and ICT have been used to improve memory and learning abilities in experimental Alzheimer’s disease models [ 19 , 20 ]. Furthermore, ICT has also been indicated to reveal an anti-inflammatory property and adjust a chloride influx in mouse brain cortical cells [ 21 ] or act as an antioxidant agent to prevent neuronal cells against oxidative stress [ 22 ]. Zhu et al [ 23 ] and Xiong et al [ 24 ] have shown that ICA treatment can protect the brain from ischemia–reperfusion injury in mice and rats, respectively.…”
Section: Introductionmentioning
confidence: 99%